PolyQ length-dependent metabolic alterations and DNA damage drive human astrocyte dysfunction in Huntington's disease. (June 2023) - Lange, Jenny; Gillham, Olivia; Flower, Michael; Ging, Heather; Eaton, Simon; Kapadia, Sneha; Neueder, Andreas; Duchen, Michael R.; Ferretti, Patrizia; Tabrizi, Sarah J.
Abstract: Huntington's Disease (HD) is a neurodegenerative disease caused by a polyglutamine (polyQ) expansion in the Huntingtin gene. Astrocyte dysfunction is known to contribute to HD pathology, however our understanding of the molecular pathways involved is limited. Transcriptomic analysis of patient-derived PSC (pluripotent stem cells) astrocyte lines revealed that astrocytes with similar polyQ lengths shared a large number of differentially expressed genes (DEGs). Notably, weighted correlation network analysis (WGCNA) modules from iPSC derived astrocytes showed significant overlap with WGCNA modules from two post-mortem HD cohorts. Further experiments revealed two key elements of astrocyte dysfunction. Firstly, expression of genes linked to astrocyte reactivity, as well as metabolic changes were polyQ length-dependent. Hypermetabolism was observed in shorter polyQ length astrocytes compared to controls, whereas metabolic activity and release of metabolites were significantly reduced in astrocytes with increasing polyQ lengths. Secondly, all HD astrocytes showed increased DNA damage, DNA damage response and upregulation of mismatch repair genes and proteins. Together our study shows for the first time polyQ-dependent phenotypes and functional changes in HD astrocytes providing evidence that increased DNA damage and DNA damage response could contribute to HD astrocyte dysfunction. Graphical Abstract: ga1 Highlights: Astrocytes contribute to disease progression in HD, but few studies have made use of pluripotent stem cell (PSC) models. WGCNA analysis found significant overlap of dysregulated modules between PSC-derived astrocytes and human HD post mortem tissue. All HD astrocyte lines exhibited upregulation of GFAP, increased cell death and DNA damage independent of polyQ length. Metabolic activity was polyQ length dependent, as astrocytes with short polyQ lengths (45-58Q) were hyperactive. Conversely, in astrocytes with long polyQ lengths (125Q, 180Q) metabolism was significantly reduced.